ANALYSIS OF THE UV SOLAR IRRADIANCE FOR THE SYNTHESIS OF PRE-VITAMIN D3 ON THE SKIN, IN ROSARIO, ARGENTINA - A. Ipiña; G. López-Padilla; A. L. Fisanotti; M. Dávalos; R. D. Piacentini (Anales (Asociación Física Argentina), 2022)
In the last years, the study of vitamin D has raised due to the increase in the incidence of people who have deficient levels of this vitamin. Few foods contain vitamin D3 naturally, the main source of obtaining the ultraviolet (UV)solar radiation, which triggers the synthesis on the skin’s surface. In this study, the effective UV solar irradiance for the synthesis of pre-vitamin D3 was determined in Rosario city, Argentina, using three methods: a) ProportionalityCoefficient, b) Herman’s equation and c) TUV model. The values were compared in clear sky conditions at solar noon.The Solar Exposure Times (TES) that reach the minimum doses of solar UV radiation for the synthesis of pre-vitamin D3 and erythema were calculated, along the period june 2019 - may 2020. The variation of the TES to accumulate the minimum dose of pre-vitamin D3 and erythema with a photoexposure of 25 % of the body (face, neck and arms) is discussed